EXPLORING EFL STUDENT TEACHERS READINESS AND GENDER DIFFERENCES OF LEARNER AUTONOMY - Fauzi C.; Basikin, M. Ed; Duisenbayeva Sh.; Kassymova, G. (Scientific Journal of Pedagogy and Economics, 2020)
Despite its importance for successful English as a Foreign Language (EFL) language learning and the abundance of scientific works of learner autonomy, this construct has not received decent attention in the Indonesian context. Further, gender differences in learner autonomy as an essential variable that has not been well-researched were also included in this study. The authors conducted a mix-method study to explore the fourth-year student teachers’ conceptualization, attitudes, and readiness for learning autonomy by employing a 43 items questionnaire survey adapted from Karabiyik (2008) to a total of 120 participants (156 male and 164 female) and interview questions to 6 volunteers. The qualitative data implied that the participants had an insufficient understanding of learner autonomy even though they exhibited a positive attitude towards this construct. The overall results of quantitative data suggested that the student teachers were not ready for learner autonomy indicated by the tendency to teacher-centered teaching which might be accounted for by low proficiency in English reflected by low engagement virtually in the majority of the autonomous learning activities. Furthermore, in terms of gender differences in learner autonomy, the t-test results demonstrated that no significant differences between male and female student teachers in terms of the responsibilities of autonomous learning, decision-making abilities, and engagement of autonomous learning outside the class. However, a significant difference was found between genders and engagement in autonomous activities in class which favored male students than their female counterparts suggesting that the male students performed more than male students in asking questions to teachers and taking opportunities to practice their English with their peers. The authors concluded that the student teachers were not ready for autonomous learning even though they had a positive attitude. Thus, the authors recommended the teachers to implement teaching methods, for instance, Project-Based Learning which might help to promote learner autonomy in the Indonesian context.